Reducing Distortions in International Commodity Markets - Hoekman, Bernard; Martin, Will (World Bank, Washington, DC, 2012)
World commodity markets and particularly the markets for agricultural commodities remain highly distorted despite the wave of liberalization that has swept world trade since the 1980s. Commodity markets are distorted on both the export and the import sides, with serious implications for world prices and their volatility. Very few of the price distortions found in commodity markets can be justified on the grounds of dealing with market failures. Rather, most policies that affect commodity prices are designed to transfer resources to favored groups by raising or lowering prices. Policies may target the level and/or the volatility of prices, and the pursuit of one type of policy objective may have unintended consequences in generating further distortions. Moreover, some commodity markets are characterized by imperfect competition. Where monopolies or oligopolies in trade arise, either because of government regulation or through other barriers to entry, distortions may arise that call for application of antitrust laws and other forms of pro-competitive policy action.